English English: Indonesia - Fitriani Fitriani; Bustanul Arifin; Fembruari Erry Prasmatiwi; R Hanung Ismono; Dyah Aring Hepiana Lestari; Sutarni Sutarni; Didik Kuswadi (Politeknik Negeri Lampung., 2022)
This study conducted to analysis the unsustainable risk of coffee farming based on the farmer’s perspective. The field survey set with questioner as a tool in exploring the farmers’ condition. The method of analysis applied Chi-square and regression model. The results indicated that coffee farmer’s perspectives on risk significantly differ based on the education level. Environment risk conditions referred to land degradation, decrease water quality, and water shortage, biodiversity loss, and global warming impact. The economics risk referred to land certainty and decrease of yield (failure). On the other side, the coffee farming income has determined by land area, a number of coffee trees, land tenure, and the participation in the certification scheme.